[Pool at Lýsuhóll] - Streng, Evelyn Fiedler (1975)
Photograph of a pool at Lýsuhóll on Snæfellsnæs Peninsula. The rectangular pool sits surrounded by wire fences and mothers with their children. The pool sits in a grassy plain of hills visible in the background. Two dark buildings, one with a beige roof is visible in the background to the left. The sky is covered in grey clouds.